2017
DOI: 10.1037/xlm0000310
|View full text |Cite
|
Sign up to set email alerts
|

There are limits to the effects of task instructions: Making the automatic effects of task instructions context-specific takes practice.

Abstract: Unlike other animals, humans have the unique ability to share and use verbal instructions to prepare for upcoming tasks. Recent research showed that instructions are sufficient for the automatic, reflex-like activation of responses. However, systematic studies into the limits of these automatic effects of task instructions remain relatively scarce. In this study, the authors set out to investigate whether this instruction-based automatic activation of responses can be context-dependent. Specifically, participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 38 publications
3
32
0
1
Order By: Relevance
“…A paradigmatic case of automaticity is the Stroop task, in that participants rigidly apply well-practiced word reading procedures to the stimuli and have difficulty in taking the more novel context (the instruction to name the ink color) into account. This difficulty is even more true for intention-based reflexivity, in that dozens of practice trials may be required for performance to become somewhat context-sensitive (Braem et al, 2016). Specifically, in the Braem et al (2016) study it was shown that a word in a task-irrelevant location triggered intention-based reflexivity when the task was novel, but that this effect went away with extensive practice.…”
Section: Evidence That Ritl Is Implemented Via Prepared Reflexesmentioning
confidence: 99%
See 1 more Smart Citation
“…A paradigmatic case of automaticity is the Stroop task, in that participants rigidly apply well-practiced word reading procedures to the stimuli and have difficulty in taking the more novel context (the instruction to name the ink color) into account. This difficulty is even more true for intention-based reflexivity, in that dozens of practice trials may be required for performance to become somewhat context-sensitive (Braem et al, 2016). Specifically, in the Braem et al (2016) study it was shown that a word in a task-irrelevant location triggered intention-based reflexivity when the task was novel, but that this effect went away with extensive practice.…”
Section: Evidence That Ritl Is Implemented Via Prepared Reflexesmentioning
confidence: 99%
“…This difficulty is even more true for intention-based reflexivity, in that dozens of practice trials may be required for performance to become somewhat context-sensitive (Braem et al, 2016). Specifically, in the Braem et al (2016) study it was shown that a word in a task-irrelevant location triggered intention-based reflexivity when the task was novel, but that this effect went away with extensive practice. Note that it is also possible that the task set was refined over time through practice, eventually resulting in a complex task set that more effectively filtered out distracting stimuli.…”
Section: Evidence That Ritl Is Implemented Via Prepared Reflexesmentioning
confidence: 99%
“…The study of intention-based reflexivity mainly uses procedures in which the automatic effect of new and merely instructed Stimulus-Response (S-R) mappings is measured (e.g., Braem et al, 2017;Cohen-Kdoshay & Meiran, 2007Liefooghe et al, 2012Liefooghe et al, , 2013Liefooghe et al, , 2016Meiran et al, 2015aMeiran et al, , 2015bTheeuwes et al, 2014;Wenke et al, 2007Wenke et al, , 2009Wenke et al, , 2015. For instance, Liefooghe et al (2012) presented participants with different runs of trials on which two tasks had to be performed that shared stimuli and responses: the inducer and the diagnostic task.…”
Section: Automatic Effects Of Instructionsmentioning
confidence: 99%
“…Results showed significant RE congruency effects (quicker font decisions to stimuli that were expected to be produced by a given response according to the instructions), suggesting that the RE instructions allowed for backward activation of responses by the effect stimuli (e.g., Q, R). Braem, Liefooghe, De Houwer, Brass, and Abrahamse (2017) showed that instructions have automatic effects even when the diagnostic task is presented in a different context (screen location) than the instructions and the inducer task. Last, AEI can involve abstract rules and not be restricted to stimulus-response rules.…”
Section: Powerful Instructions 10mentioning
confidence: 99%
“…Many questions remain unanswered such as what is the relationship between skill-based automaticity and AEI (Braem et al, 2017) and what are the relative constraints, advantages and disadvantages of each form of automaticity? Recent research on the neural basis of rapid learning from instructions (Cole, Laurent, & Stocco, 2013) should also be extended to explain AEI (Brass, Liefooghe, Braem, & De Houwer, in press; Cole, et al, in press).…”
Section: Powerful Instructions 12mentioning
confidence: 99%